Factors affecting functional disability in patients with non-specific chronic low back pain: a cross-sectional study - Zhang, Shenyue; Yang, Huan; Luo, Beier; Cheng, Yajun; Niu, Shengbo; Yang, Changwei (Frontiers in Neurology, 2024)
Knowledge about factors affecting functional disability in patients with nonspecific chronic low back pain (NSCLBP) is helpful in guiding treatment, but there has been little systematic research on this topic. The aim of this study was to identify independent factors contributing to functional disability in patients with NSCLBP, especially the impact of sagittal parameters and body postures in work, learning and daily life.Methods: Sociodemographic data, sagittal parameters, Oswestry Disability Index (ODI), Numeric Rating Scale (NRS) and 36-item Short Form Health Survey (SF-36) of NSCLBP patients were collected. Patients were divided into a low functional disability group (ODI ≤ 20) and a high functional disability group (ODI > 20), and ODI was converted to Ranked ODI (RODI) accordingly. Sociodemographic data, sagittal parameters, NRS, SF-36 were compared by univariate analysis between the two groups. Correlation analysis of them with RODI were conducted. The sociodemographic data and sagittal parameters related to RODI were analyzed by logistic regression to select potential RODI-associated factors. The level of significance was set at P ＜ 0.05. Results: Age, educational background, daily main posture while working or learning (DMPWL), daily standing time while working or learning (DSTTWL), daily sitting time while resting (DSITR), sacral slope-pelvic tilt (SS-PT), spinosacral angle (SSA), NRS, MH) were different between the two groups (P ＜ 0.05). Correlation analysis showed that they were related to RODI (P ＜ 0.05). The logistic regression analysis indicated that the regression coefficients of college degree, postgraduate diploma, DSITR and SSA were (B = -0.197, P = 0.003), (B = -0.211, P = 0.006), (B = -0.139, P = 0.039), and (B = -0.207, P = 0.001), respectively, and the odds ratio (OR) and 95% confidence interval (CI) were 0.489 (0.308, 0.778), 0.299 (0.125, 0.711), 0.875 (0.772, 0.993), and 0.953 (0.925, 0.981), respectively.Educational background, DSITR and SSA are independent factors affecting functional disability of NSCLBP patients. NSCLBP patients with a lower educational background, shorter DSITR or smaller SSA should be taken into account in clinical practice and therapeutic choices. Extending sitting time for rest and avoidance of a forward-leaning standing position are beneficial for reducing functional disability of NSCLBP.